Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1159/000369255
|View full text |Cite
|
Sign up to set email alerts
|

Dose Escalation and Pharmacokinetic Study of Carboplatin plus Pemetrexed for Elderly Patients with Advanced Nonsquamous Non-Small-Cell Lung Cancer: Kumamoto Thoracic Oncology Study Group Trial 1002

Abstract: Objectives: This study was designed to determine the recommended dose of carboplatin and pemetrexed for elderly (≥70-year-old) chemotherapy-naïve patients with advanced nonsquamous non-small-cell lung cancer (NSCLC) and to investigate the pharmacokinetics of pemetrexed. Methods: The patients were treated with 4-6 cycles of carboplatin plus a fixed dose of pemetrexed (500 mg/m2) every 3 weeks; the dose of carboplatin was escalated [from area under the curve (AUC) 4 to AUC 6]. To examine the pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…To date, the median OS values reported with nab -paclitaxel/carboplatin treatment of elderly patients in this study and in the elderly subset of the phase 3 trial are among the longest reported in elderly patients with advanced NSCLC. It should be noted that studies of pemetrexed/carboplatin have indicated that a carboplatin dose of AUC 5 may be more tolerable in this population ( 10 , 11 ). However, other large studies of taxane-based doublets have routinely examined carboplatin AUC 6 in elderly patients ( 4 , 5 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the median OS values reported with nab -paclitaxel/carboplatin treatment of elderly patients in this study and in the elderly subset of the phase 3 trial are among the longest reported in elderly patients with advanced NSCLC. It should be noted that studies of pemetrexed/carboplatin have indicated that a carboplatin dose of AUC 5 may be more tolerable in this population ( 10 , 11 ). However, other large studies of taxane-based doublets have routinely examined carboplatin AUC 6 in elderly patients ( 4 , 5 , 9 ).…”
Section: Discussionmentioning
confidence: 99%